Finite Element Analysis of Micro Beam in a MEMS-Based Microfluidic Channel - Ertugrul, Ishak (Mehmet BULUT, 2020)
It is well known that the physical properties of a micro beam are largely dependent on the fluid and micro channels in which the beam is immersed. In this study, the finite element analysis of the micro beam within the microfluidic channel based on MEMS (Micro-Electro-Mechanical Systems) is aimed to be made in detail. These analyzes include von Mises stress, pressure quantities, velocities, and displacements during movement. Using the Euler-Bernoulli equation for the beam, a micro-beam fixed in a fluid is modeled and analyzed. Unstable Stokes equations are solved using a Helmholtz decomposition technique in a two-dimensional plane containing micro-beam sections. The finite element method using the Comsol Multiphysics software results is compared with the current validation method, and an acceptable match is obtained between them. Pressure, velocity, and displacement analyzes were created by ensuring all boundary conditions. The current formulation has been shown to be a suitable and novel approach to solve the problem with good accuracy. As a result, a theoretical model is provided that can be used in the design and interpretation of density, viscosity, and microfluidic sensors.

Bir mikro kirisin fiziksel özelliklerinin, kirisin içerisine daldirildigi siviya ve mikro kanallara büyük ölçüde bagli oldugu iyi bilinmektedir. Bu çalismada, MEMS (Mikro Elektro-Mekanik Sistemler) tabanli mikroakiskan kanal içerisindeki mikro kirisin sonlu elemanlar analizleri ayrintili bir sekilde yapilmasi amaçlanmistir. Bu analizler von Mises gerilimi, basinç miktarlari, hareket sirasinda olusan hizlar ve yer degistirmeleri kapsamaktadir. Kiris için Euler-Bernoulli denklemi kullanilarak akiskan içinde sabit bir mikro kiris modellenerek analizi yapilmistir. Kararsiz Stokes denklemleri, mikro kiris kesitlerini içeren iki boyutlu bir düzlemde bir Helmholtz ayristirma teknigi kullanilarak çözülmektedir. Comsol Multiphysics yazilim sonuçlarini kullanan sonlu elemanlar yöntemi, dogrulama için mevcut yöntemle karsilastirilmis ve aralarinda kabul edilebilir bir eslesme elde edilmistir. Basinç, hiz ve yer degistirme analizleri tüm sinir kosullari saglanarak olusturulmustur. Mevcut formülasyonun, sorunu iyi bir dogrulukla çözmek için uygun ve yeni bir yaklasim oldugu gösterilmistir. Sonuç olarak çalismada, yogunluk, viskozite ve mikroakiskan sensörlerinin tasariminda ve yorumlanmasinda kullanilabilecek teorik bir model saglanmistir.
MEMS Tabanli Bir Mikroakiskan Kanaldaki Mikro Kirisin Sonlu Elemanlar Analizi
Keywords: Engineering; Mühendislik